Methodological toolkit for economic diagnostics of marketing activities of a development company - Maksymiuk , Yu. S. (Ways to Improve Construction Efficiency, 2023)
New directions of marketing are associated with phenomena such as globalization, international cooperation, "internetization", accelerated development of technologies and means of communication. Development companies should identify the buyer as a person and focus more on the inner world of a person. This requires new approaches to marketing activities and management as a whole. The economies of the countries are closely interconnected and interdependent. Trade is conducted with the help of the Internet and mobile phones, through which information is transmitted instantly, which provides advantages for the consumer in terms of lowering prices, speeding up production and delivery of goods and services to the right place at the right time. However, there is a flip side – events or changes in situations in one country can spread and affect many other countries and create large-scale instability with unpredictable results. In conditions of competition and an unstable market, effective management of economic activity is achieved not only at the expense of external sources, but also at the expense of improving the internal structure. Establishment of control, reduction of production costs, search and retention of qualified personnel, improvement of service quality. Determining the main changes in the marketing environment should be the primary goal of managing the marketing activities of development enterprises, because interest and budget are affected by changes that occur in the surrounding environment. New forms of communication, means of information transmission, advertising, etc. appear. Customers are more informed, competitive advantages are short-lived, a new product can be quickly copied, the Internet and social networks create sources of information and new methods of sales. Marketing strategies that are recommended to development companies in times of uncertainty and fluctuations in the economy are: provision of the target consumer segment with necessary construction products; looking for an opportunity to increase the marketing budget and abandon ineffective programs. The basis of management of the marketing activities of development enterprises in the conditions of the modern market are the values of society, the satisfaction of the needs of buyers and the profitability of the enterprise.